2006
DOI: 10.2174/138161206777698710
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Angiogenesis by the Kallikrein-Kinin System

Abstract: High molecular weight kininogen (HK) is a plasma protein that is cleaved by plasma kallikrein in the clinical settings of sepsis and chronic inflammatory diseases such as rheumatoid arthritis and Crohn's disease. This proteolytic event results in a nonapeptide, bradykinin (BK), and a kinin-free derivative of HK, namely HKa. BK promotes angiogenesis by upregulation of bFGF through the B1 receptor or by stimulation of VEGF formation via the B2 receptor. Kininogen-deficient rats show diminished angiogenesis when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 81 publications
4
38
0
2
Order By: Relevance
“…HKa exerts its antiproliferative effects on subconfluent, actively proliferating endothelial cells on a provisional extracellular matrix such as vitronectin (19). We therefore seeded human umbilical vein endothelial cells (HUVEC) onto vitronectin-coated plates at subconfluent density and then either left them untreated or treated them with HKa.…”
Section: Ferritin Blocks Effects Of Hka On Endothelialmentioning
confidence: 99%
“…HKa exerts its antiproliferative effects on subconfluent, actively proliferating endothelial cells on a provisional extracellular matrix such as vitronectin (19). We therefore seeded human umbilical vein endothelial cells (HUVEC) onto vitronectin-coated plates at subconfluent density and then either left them untreated or treated them with HKa.…”
Section: Ferritin Blocks Effects Of Hka On Endothelialmentioning
confidence: 99%
“…The influence of kinins in angiogenesis has recently been appreciated. Kinin promotes angiogenesis by upregulation of basic fibroblast growth factor through bradykinin -B1 receptor and by stimulation of VEGF formation by bradykinin both B1 and B2 receptors [28], and kinins may act synergistically with TGF-β1 [7]. Our recent study [29] strongly indicated that both kinin receptors are present in intestinal layers in human IBD and that B1 receptor is a major structural background for kinin function.…”
Section: Discussionmentioning
confidence: 86%
“…Kinins released into synovial fluid by the proteolytic action of kallikreins on kininogens on the surface of neutrophils are likely to cause vasodilatation and pain, increase vascular permeability, promote leukocyte margination and stimulate cytokine release from monocytes [17,29]. Pain, the predominant symptom in kOA, is multidimensional in its nature and mediated through a variety of factors as bradykinin [30][31][32][33].The RAS is best known as a major regulator of blood pressure, but it also is important at the micro vascular level in the regulation of neovascularization [34,35]. In addition, the RAS has important modulatory activities in the process of kOA [24].…”
mentioning
confidence: 99%